2013
DOI: 10.3389/fncom.2013.00094
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of epileptic activity by deep brain stimulation: a model-based study of frequency-dependent effects

Abstract: A number of studies showed that deep brain stimulation (DBS) can modulate the activity in the epileptic brain and that a decrease of seizures can be achieved in “responding” patients. In most of these studies, the choice of stimulation parameters is critical to obtain desired clinical effects. In particular, the stimulation frequency is a key parameter that is difficult to tune. A reason is that our knowledge about the frequency-dependant mechanisms according to which DBS indirectly impacts the dynamics of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 81 publications
1
65
0
Order By: Relevance
“…Along the same line, novel perspectives are foreseen in clinical approaches for testing neurostimulations (Kahane and Depaulis, 2010). There is indeed a growing interest in epileptology for alternative therapeutic strategies aimed at modulating the electrical brain activity via direct or indirect stimulation of the epileptic regions (Fisher, 2013;Laxpati et al, 2014;Mina et al, 2013). Computational models may help us to determine the key structures to stimulate and to find the optimal stimulation parameters.…”
Section: Discussion and Perspectivesmentioning
confidence: 98%
See 2 more Smart Citations
“…Along the same line, novel perspectives are foreseen in clinical approaches for testing neurostimulations (Kahane and Depaulis, 2010). There is indeed a growing interest in epileptology for alternative therapeutic strategies aimed at modulating the electrical brain activity via direct or indirect stimulation of the epileptic regions (Fisher, 2013;Laxpati et al, 2014;Mina et al, 2013). Computational models may help us to determine the key structures to stimulate and to find the optimal stimulation parameters.…”
Section: Discussion and Perspectivesmentioning
confidence: 98%
“…Neurostimulations are also a topic of growing interest in computational modeling. A number of NMMs have been proposed to account for the effect of electrical stimulations (i) on rhythmic self-terminating responses as observed in ECoG (Goodfellow et al, 2012a), (ii) on epileptic activity observed in focal cortical dysplasia (Mina et al, 2013) or (iii) on evoked responses as a way to link between EEG data and neuronal excitability in the perspective of anticipating seizures (Suffczynski et al, 2008). This latter field of research has also benefitted from the development of computational models.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Developing computational neurostimulation models requires the right balance of detailed multiscale model with appropriate reductionism (Douglas et al, 2015;Frohlich et al, 2015;Holt and Netoff, 2014;Karamintziou et al, 2014;Mina et al, 2013;Modolo et al, 2011;Shukla et al, 2014). This review attempts to present the modeling process as tractable, even when dealing with unknowns, including serializing modeling steps and applying the quasi-uniform assumption where relevant.…”
Section: Dealing With Unknowns and Multiscale Approachesmentioning
confidence: 98%
“…In the second category, specific models of seizure activity are first developed, and subsequently control parameters (such as inputs) are used to inform stimulation protocols to suppress the seizure activity. Parameters such as stimulation frequency can be explored in the model (Mina et al, 2013). Often, tools from control theory (the branch of engineering which investigates the effects of inputs and feedback on dynamical systems) are used, such as linear and nonlinear feedback controllers (Kramer et al, 2006).…”
Section: Figurementioning
confidence: 99%